(3fRgI GdCdHGH GdLGeYI dafhf GdBOGHs - (3YHO Gddg Hf YHO Gddg Hf SdGeg GdCOcGhj GdTGaYj GdeYQha HGdeDPfs
(3ChdgG (B:s
(3MeOkG def Rjf eMGad GdNdaGA HeMGSf GdCOHGA, hCfgV gege dGcJSGH GdeYGdj, aGcJSHhG ef MddgG OjHGLkG ePgHkG s
(3BNQgG (B:s
(3Je GdLRA GdChd ef fRgI jJdhg aj GdKGfj GdHGH GdSGHY YTQ aj NHQ GdMSGf ef GdLhGQj hGdaJjGf s
(3GdfSNI HgG MhGTs
(3fSNI QGHYI JJab aj ChdgG eY GdfSNI GdChdi HGNJdGa jSjQ aj HYV GdCdaGXs
(3HgG fXGe GdJYbjHIs
(3hHgGeTgG JbjjOGJ hJUMjMGJ s
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B6 - (3U (B139 s
Keywords: (3GdCOHs